Common law households and marriage frequency 1974_2 - Trost, Jan (Uppsala University, 1984)
The aim is that the material should illustrate the unmarried cohabitation that has been more frequent from the mid-sixties. Married couples are compared with unmarried cohabitant couples from Gävle. Questions about personal data, background to cohabitation and/or marriage, engagement and marriage, parents and knowledge about legal and social matters.

The aim is that the material should illustrate the unmarried cohabitation that has been more frequent from the mid-sixties. Married couples are compared with unmarried cohabitant couples from Gävle. Questions about personal data, background to cohabitation and/or marriage, engagement and marriage, parents and knowledge about legal and social matters.
Ogift samboende och äktenskapsfrekvens 1974_2
Keywords: Legislation and legal systems; Lagstiftning och rättssystem; Family life and marriage; Familjeliv och äktenskap; Social Sciences; Samhällsvetenskap